IL-17A contributes to myocardial ischemic injury by activating NLRP3 inflammasome in macrophages through AMPKα/p38MAPK/ERK1/2 signal pathway in mice. (January 2019) - Zhang, Lisha; Liu, Peining; Wen, Wen; Bai, Xiaofang; Zhang, Yan; Liu, Mengping; Wang, Lijun; Wu, Yue; Yuan, Zuyi; Zhou, Juan
Highlights: IL-17A activates NLRP3 inflammasome and increases IL-1β release via AMPKα/p38MAPK/ERK1/2 pathway in macrophages. IL-17A contributes to myocardial ischemic injury by facilitating macrophages infiltration and inflammasome activation in ischemic myocardium. AMPKα activation plays an unexpected pro-inflammatory role in the inflammation induced by IL-17A during acute ischemia. Abstract: Background: Acute myocardial infarction (AMI) is followed by an acute inflammation involving inflammasome activation, thereby inducing cardiac dysfunction. Interleukin-17A (IL-17A) involves in many inflammatory diseases, but its roles in inflammation following AMI are still obscure. The aim of this study is to investigate the roles of IL-17A in the inflammatory response following AMI and its underlying mechanisms. Methods and results: NLRP3 inflammasome and AMPKα/p38MAPK/ERK1/2 signaling pathway were significantly activated under the induction of IL-17A in mouse peritoneal macrophages, which could be inhibited by AMPK inhibitor compound C (CC). Both p38MAPK and ERK1/2 inhibitors could partially inhibit the activation of NLRP3 inflammasome in macrophages treated by IL-17A. In vivo, IL-17A knockout not only decreased the infiltration of macrophages and the activation of NLRP3 inflammasome and AMPKα/p38MAPK/ERK1/2 signaling pathway in ischemic myocardium, but also improved cardiac function and reduced infarction size after the ligation of descending segment from left coronary artery for 3 days in mice, while IL-17A administration further aggravated the myocardial ischemic injury, which were prevented by CC administration. Conclusion: IL-17A aggravates inflammatory response during AMI by inducing macrophages infiltration and activating NLRP3 inflammasome through AMPKα/p38MAPK/ERK1/2 pathway.